2014
DOI: 10.3168/jds.2013-7390
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of acid-hydrolyzed Citrus unshiu peel extract in milk

Abstract: Citrus fruit (Citrus unshiu) peels were extracted with hot water and then acid-hydrolyzed using hydrochloric acid. Antimicrobial activities of acid-hydrolyzed Citrus unshiu peel extract were evaluated against pathogenic bacteria, including Bacillus cereus, Staphylococcus aureus, and Listeria monocytogenes. Antilisterial effect was also determined by adding extracts at 1, 2, and 4% to whole, low-fat, and skim milk. The cell numbers of B. cereus, Staph. aureus, and L. monocytogenes cultures treated with acid-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 24 publications
0
23
0
1
Order By: Relevance
“…Plant‐derived antimicrobials have been researched and consumed frequently over the past decade to improve quality of health and provide ethnopharmacological remedies (Nittayananta, Limsuwan, Srichana, Sae‐Wong, & Amnuaikit, ; Tang, Prodhan, Biswas, Le, & Sekaran, ). Flavonoid, which is the most abundant type of polyphenolic compound found in plant materials, was studied to increase in concentration and antibacterial activity using acid hydrolysis (Min, Kim, Lee, Kim, & Paik, ), fermentation (Saleh et al, ), and silver nanoparticles (Rashid et al, ). In this study, fermentation was used to increase the antimicrobial activity of I. britannica extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant‐derived antimicrobials have been researched and consumed frequently over the past decade to improve quality of health and provide ethnopharmacological remedies (Nittayananta, Limsuwan, Srichana, Sae‐Wong, & Amnuaikit, ; Tang, Prodhan, Biswas, Le, & Sekaran, ). Flavonoid, which is the most abundant type of polyphenolic compound found in plant materials, was studied to increase in concentration and antibacterial activity using acid hydrolysis (Min, Kim, Lee, Kim, & Paik, ), fermentation (Saleh et al, ), and silver nanoparticles (Rashid et al, ). In this study, fermentation was used to increase the antimicrobial activity of I. britannica extract.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, phenolic compound compo- 2018). Flavonoid, which is the most abundant type of polyphenolic compound found in plant materials, was studied to increase in concentration and antibacterial activity using acid hydrolysis (Min, Kim, Lee, Kim, & Paik, 2014), fermentation (Saleh et al, 2018), and silver nanoparticles (Rashid et al, 2017). In this study, fermentation was used to increase the antimicrobial activity of I. britannica extract.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts should also be made for applying control measures at fish ponds since fish products may serve as an important source of listeriosis (Nakari et al 2014). Tannin-rich fraction from pomegranate rind (TFPR) and acid-hydrolyzed Citrus unshiu peel extract have been found to be effective food preservatives in reducing chances of L. monocytogenes contamination in foods Min et al 2014). Food safety control measures must be implemented properly to limit listeriosis and to ensure consistent control strategies (Oyarzabal 2006;Adzitey & Huda 2010).…”
Section: Ways To Minimize Infection In Humansmentioning
confidence: 99%
“…Citrus unshiu Markovich, which belongs to the Rutaceae family, is a citrus fruit that is readily seeded, has no seeds, and is grown in East-Asian countries, including Korea (25,26). For several hundred years, citrus and dried peel have been used as traditional medicines to treat gastrointestinal disorders, colds, indigestion, and bronchial discomfort, and pharmacological activities have been reported for inflammation, allergies, diabetes, and viral infections (27)(28)(29)(30). A study on a tumor-bearing mouse model has shown that C. unshiu peel (Chimpi) extract inhibits tumor growth, which was associated with an increased production of cytokines such as interferon-γ and tumor necrosis factor-α (31).…”
Section: Introductionmentioning
confidence: 99%